Gems : readings in Philippine literature - Perez, Rodolfo C. (Manila, Philippines : Mindshapers Co. Inc., 2015)
This book commences with old but dearly-loved and fondly-remembered myths, legends and tales from various regions in the archipelago, demonstrating our unique ethnicity. Their diversity does not fail our interest in knowing how each ethnic group views the world around it, how it attempts to explain the creation of its universe, or how it endeavors to account for the existence human beings.
Chapter 1. Philippine folk literature -- Chapter 2. Short stories -- Chapter 3. Poetry -- Chapter 4. Prose narrative (articles and essays) -- Chapter 5. The novel (excerpts) -- Chapter 6. The drama.
Includes bibliographical references.
Keywords: PHILIPPINE LITERATURE (ENGLISH)